Retina Image and Bat-Inspird Algorithm for Artificial Key Generation (Medico Legal Update, 2020)
The process of key generation is utilized in different applications based on encryption techniques. Thecharacteristics of the generated key should satisfy the required security as potential. The traditionaltechniques used for generating keys are based on various equations based on chaos maps or modulation formaking these keys as one-time pads. Also, there are many techniques that utilized the block cipher or hashfunction for generating keys. In this paper, a retina image and bat-inspired algorithm are used for generatingsecure keys. Several processes have been applied to the input retina images like enhancement and edgedetection processes. In the proposed technique, some parameters are adjusted for controlling the results andevery output represents a bat solution and depending on the fitness function, the keys are generated. Thesegenerated keys are tested and evaluated using NIST tests. As a case study, some images are encrypted usingthe generated keys and the obtained encrypted images passed all the required security tests.